Geographic allocation of OSS contributions: the role of institutions and culture - Sebastian von Engelhardt; Andreas Freytag (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
So-called open source software (OSS) is marked by free access to the software and its source code. Copyright-based OSS licenses permit users to use, change, improve and redistribute the software, which is designed and developed in a public, collaborative manner. High quality OSS products like Linux, Apache etc. are developed by thousands of volunteers, who often do not receive direct monetary reward. Thus, OSS seems to be an example of a `private provision of a public good', and some argue that OSS is a `new intellectual property paradigm' for the digital economy. Therefore, OSS has been in the focus of economic research for some years. However, it is still not known which institutional and cultural factors favor OSS development, although the differences of countries in OSS activities can not be solely explained by GDP, education and internet access. For this reason, we perform a cross-country study analyzing how the number of OSS developers per inhabitants and the level of OSS activity of a country depends on institutional and cultural factors. We make use of data about OSS developers registered at SourceForge, and are able to assign 94% of them to their countries. We then run regressions with several institutional and cultural factors. Our findings are that a culture characterized by individualism/self-determination is in favor of OSS. Also, social capital in terms of interpersonal trust has a positive impact on the number of OSS developers as well as on the OSS activity level. The openness to novelty is relevant only with respect to scientific progress, i.e. an optimistic view of scientific progress is significantly positive. While the attitude towards competition was never significant, less regulated countries have more OSS activists and activity. Furthermore, the protection of intellectual property rights has (if all) a positive impact. Our study contributes to the understanding of the impact of cultural and institutional factors in general as well as in particular with respect to OSS. Additionally it also improves the understanding of OSS. OSS has similarities to technical science and scientific culture, is a a public good game with the contributions are a means to an end. OSS is a new intellectual property right paradigm and is based on an entrepreneurial spirit.
Keywords: B52; L17; L86; O34; Z13; Z19; 330; Open Source; Culture; Institutions; Social Capital; Trust; Regulation; Entrepreneurial Spirit; Individualism; Intellectual Property Rights; Open Source; PC-Software; Programmierung; Individualismus; Unternehmer; Wirtschaftsethnologie; Immaterialgüterrechte; Regulierung; Welt